If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.4 = (m + 4) Reorder the terms: 2.4 = (4 + m) Remove parenthesis around (4 + m) 2.4 = 4 + m Solving 2.4 = 4 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 2.4 + -1m = 4 + m + -1m Combine like terms: m + -1m = 0 2.4 + -1m = 4 + 0 2.4 + -1m = 4 Add '-2.4' to each side of the equation. 2.4 + -2.4 + -1m = 4 + -2.4 Combine like terms: 2.4 + -2.4 = 0.0 0.0 + -1m = 4 + -2.4 -1m = 4 + -2.4 Combine like terms: 4 + -2.4 = 1.6 -1m = 1.6 Divide each side by '-1'. m = -1.6 Simplifying m = -1.6
| -7(2+2x)=-70 | | 4x+3(-2x-7)=-7 | | 7a+10a+7a+12a=360 | | -(9-5n)= | | -2(4+m)+6(m-3)=14 | | 4(5x-4)+10=-3 | | 20+8(11-q)=-12 | | 240=126-v | | 6x-12x+9=-27 | | -24-5x=-4(x+5) | | y=101.21x+0.0991 | | 2(3*-0.5+2)-2*-0.5=6*-0.5+5 | | 3(4j-3)8=-1+12j | | 12a+99a=3885 | | -11u-6=3u^2 | | 32-8p=-8(4p+2) | | 7+x=8x-2 | | -7-3v-10+3v=0 | | 5x+48=3x-36 | | 2(3*0.5+2)-2*0.5=6*0.5+5 | | 11x^2y^2=33x^2y | | 3(6s+12-10s-6)=0 | | 3(3n+4)=54+6x | | -5.2+9=-8 | | 22r+10-2= | | (x+7).3=33 | | 15-5x=-40 | | -5.8+9=-8 | | 2(3x+2)-2x=6x+5 | | X-45+45=540 | | .01x+.04y=-10 | | 5*x=-20 |